Analysis of the Capacity of the Public Health System in Reducing the Health Impact of Natural Disasters - Sri Hazanah; Nora Harminarti (CV. Get Press Indonesia, 2026)
Climate change has intensified natural disasters, straining health systems and threatening public health service sustainability. This study analyzes public health system capacity to mitigate disaster health impacts and identifies influential components. Employing a quantitative descriptive-analytical, cross-sectional design, the research targeted disaster-prone Indonesian areas across three high-risk districts/cities. The population comprised disaster-response health facilities; a purposive sample of 90 facilities was selected. Data came from structured 30-item, 5-point Likert-scale questionnaires assessing five capacity components: human resources, infrastructure, information/surveillance, logistics/financing, and governance/coordination. Analysis used descriptive statistics, Pearson correlation, and multiple linear regression (95% significance). Results revealed moderate capacity, with information/surveillance as the primary weakness. Disaster health impacts were high, especially service access disruptions and essential service interruptions. Correlation indicated a significant negative link between capacity and impacts. Regression showed capacity explaining 48% of impact variation, with governance/coordination as the strongest predictor. Findings underscore strengthening governance, integrating health information systems, and enhancing cross-sector coordination to boost health system resilience against disasters.